A NEW SPECIES OF ANISOPTERA (Dipterocarpaceae) II - ANWARI DILMY (Research Center for Biology, 1960)
Some new material of Anisoptera kostermansiana Dilmy, described by the present author in Reinwardtia 3: 347. 1956, was put at his disposal by the kindness of Mr. J. S. Womersley, Chief, Division of Botany at Lae, T.N.G.